Segregation kinetics of miktoarm star polymers: A dissipative particle dynamics study - Gogoi D.; Puri S.; Chauhan A.; Singh A. (My University, 2025)
We study the phase separation kinetics of miktoarm star polymer (MSP) melts/blends with diverse architectures using dissipative particle dynamics simulation. Our study focuses on symmetric and asymmetric miktoarm star polymer (SMSP/AMSP) mixtures based on arm composition and number. For a fixed MSP chain size, the characteristic microphase-separated domains initially show diffusive growth with a growth exponent φ∼1/3 for both melts that gradually crossover to saturation at late times. The simulation results demonstrate that the evolution morphology of SMSP melt exhibits perfect dynamic scaling with varying arm numbers; the timescale follows a power-law decay with an exponent θ≃1 as the number of arms increases. The structural constraints on AMSP melts cause the domain growth rate to decrease as the number of one type of arms increases while their length remains fixed. This increase in the number of arms for AMSP corresponds to increased off-criticality. The saturation length in AMSP follows a power-law increase with an exponent λ≃2/3 as off-criticality decreases. Additionally, macrophase separation kinetics in SMSP/AMSP blends show a transition from viscous (φ∼1) to inertial (φ∼2/3) hydrodynamic growth regimes at late times; this exhibits the same dynamical universality class as linear polymer blends, with slight deviations at early stages. © 2024 American Physical Society.